The Pain of Modern Life: The Misery of Modern Existence - Meltem Ince Yenilmez; Eylül Kabakçı Günay (Research on Ageing and Social Policy, 2024)
Social isolation and loneliness are posing more problems than ever. There are concerns that the long-term effects of loneliness will be felt when the COVID-19 outbreak reaches its third year. This study examines the prevalence and components of social isolation and loneliness across Europe. This study seeks to understand the effects of loneliness within a broad framework that may be used to guide anti-loneliness measures. This study also looks at why loneliness is important to study, the connection between loneliness and social isolation, future research on the topic, and interventions that could help with the problem of unequal exposure to loneliness and lack of assistance because of one's socioeconomic status.